ANALISIS FORENSIK DIGITAL PADA KASUS CYBERBULLYING DENGAN METODE NATIONAL INSTITUTE OF STANDARD AND TECHNOLOGY SP 800-86 - Dasmen, Rahmat Novrianda; Muhammad Reihan Pratama; Yasir, Husni; Budiman, Ariff (JURNAL ILMIAH INFORMATIKA, 2024)
Rapidly developing technology is in line with criminal acts that have increased dramatically, one of the criminal acts that often occur in the digital world is cyberbullying, until the evidence of the event is successfully removed so that it is necessary to search and recover digital data that has been removed to be used as digital evidence, this process is commonly known as digital forensics. Investigation of digital evidence is carried out by applying one of the methods, namely the National Institute of Standard and Technology SP 800-86 (NIST SP 800-86) through stages starting from collecting evidence, analyzing, searching for data, and recovering found data, to validating files with digital flashdisk evidence sources using Autopsy forensic tools. The results of this study show that the use of Autopsy is able to analyze and restore digital evidence previously stored on a flashdisk with a 100% success rate, the data that was successfully recovered consisted of 4 files with the PNG extension and 1 file with the MP4 extension according to the designed case scenario.